Stochastic cooperative advertising in a manufacturer-retailer decentralized supply channel - Peter E. Ezimadu; Chukwuma R. Nwozo (Journal of Industrial Engineering International, 2017)
This work considers cooperative advertising in a manufacturer-retailer supply chain. While the manufacturer is the Stackelberg leader, the retailer is the follower. Using Sethi model it models the dynamic effect of the manufacturer and retailer's advertising efforts on sale. It uses optimal control technique and stochastic differential game theory to obtain the players' advertising strategies and the long-run value of the awareness share. Further, it models the relationship between the payoffs of both players and the awareness share. The work shows that with the provision of subsidy the retail advertising effort increases while the manufacturer's advertising effort reduces. It further shows that the total channel payoff is higher for subsidised retail advertising. However, the subsidy can only be possible if the rate of growth of the manufacturer's payoff is twice higher than that of the retailer.
Keywords: 650; Supply chain; Cooperative advertising; Stochastic differential game; Subsidy; Sethi model; Optimal control